Middle Darebin Creek concept plan : Settlement Road, Bundoora, to the SEC transmission line easement, Epping (Melbourne Parks & Waterways, 1994)
Consists of two parts: The concept plan document which sets out the recommended actions to achieve the vision and the aims of the plan and; a separate resource document which gives details of the vegetation of the area and information on water quality.